The effect on the shallow aquifer system of the planned undersea subway linking Venice to Marco Polo Airport (Italy) - Antonelli, Renzo; Colleselli, Giuseppe; Cultrera, Matteo (Italian journal of engineering geology and environment, 2009)
The design of the undersea subway named “Sublagunare” joining “Marco Polo” Airport to the city of Venice has required specific research in order to evaluate the environmental impact on the lagoon subsoil. Past geognostic investigations and hydraulic tests have provided a satisfactory geologic and hydrogeologic setting of the area. A finite element 3-D model has been applied to the most critical tract of the planned tunnel. The flow model results have provided a set of predictions about hydraulic head distribution imposing more or less favourable boundary conditions. The numerical analyses have been encouraging as they give evidence of compatibility with the margin of safety requested by the tunnel design and with the protection of the natural environment.